2013
DOI: 10.3174/ajnr.a3708
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in the Utilization of Mechanical Thrombectomy for Acute Ischemic Stroke in US Hospitals

Abstract: BACKGROUND AND PURPOSE:Previous studies have demonstrated that socioeconomic disparities in the treatment of cerebrovascular diseases exist. We studied a large administrative data base to study disparities in the utilization of mechanical thrombectomy for acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
2
40
2
Order By: Relevance
“…These findings are similar to those by Brinjikji et al in 2013. 12 Their study included 371 cases and found a .59 lower odds of thrombectomy utilization in AA, compared with NHW (P<.001).…”
Section: Discussionmentioning
confidence: 95%
“…These findings are similar to those by Brinjikji et al in 2013. 12 Their study included 371 cases and found a .59 lower odds of thrombectomy utilization in AA, compared with NHW (P<.001).…”
Section: Discussionmentioning
confidence: 95%
“…[31][32][33] Among adult stroke patients, African-Americans, the uninsured, and Medicare patients have been shown to be less likely to receive endovascular therapy. 34 The impact of insurance status, socioeconomic status, and race on pediatric stroke interventions, access to care, and outcomes is an area that warrants further study. Seizure was less common in the endovascular therapy group, which may be explained by the higher rates of seizures in younger children in this cohort, consistent with other reports in pediatric stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Brinjikji et al 2 found that patients of lower socioeconomic status were less likely to undergo elective treatment of unruptured aneurysms that those of higher socioeconomic status. Patients of lower socioeconomic status are also less likely to receive intravenous tissue plasminogen activator and mechanical thrombectomy for acute ischemic stroke 5 15 16. Amaranto et al 17 demonstrated that Caucasian race was an independent predictor of surgical intervention for the treatment of carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%